Optimization and cost-benefit assessment of hybrid power systems for off-grid rural electrification in Ethiopia - Gebrehiwot, K.; Mondal, A.H.; Ringler, Claudia; Getaneh-Gebremeskel, A. (Elsevier, 2019)
Standalone solar photovoltaic systems are increasingly being distributed in Ethiopia, but these systems are sub-optimal due to their intermittent power supply. A hybrid system that integrates and optimizes across solar photovoltaic and complementary energy sources, such as wind and diesel generation, can improve reliability, and reduce the unit cost of power production. This study assesses the potential of a hybrid system to electrify a remote rural village in Ethiopia. The Hybrid Optimization of Multiple Electric Renewables model is used to assess primary data, develop a load profile and identify the optimal least-cost system option for the village. A sensitivity analysis was performed to determine the effect of variations in solar radiation, wind speed, and diesel price on optimal system configurations. The results show that a hybrid system with a combination of photovoltaic array, wind turbine, battery and diesel generator is the best option from an economic point of view. To meet the village's daily peak demand of 19.6 kW, energy generation cost is estimated at 0.207 dollars per kilowatt hour and net present cost at 82,734 dollars. The optimal system allows for a reduction of 37.3 tons of carbon dioxide emissions per year compared with diesel-only electricity generation.